2019
DOI: 10.1016/j.erss.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Carbon or cash: Evaluating the effectiveness of environmental and economic messages on attitudes about wind energy in the United States

Abstract: Public support or opposition to the expansion of wind energy plays a key role in energy policy and the development of the industry. For more than 30 years, scholars have attempted to understand the nature of public opinion about wind energy. Unfortunately, the largely observational and correlational nature of the evidence limits the abilities of scholars to isolate the causal relationships that shape attitudes about wind energy. Recent summaries of the literature illustrate the need for experimental designs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The share of liberals among early adopters of private solar panels was higher than the share of conservatives [12]. Liberal ideology and orientation to liberal parties was associated with elevated support for renewable energy projects and policies, as well as with stronger support for the Swiss Energy Act [3,13,14].…”
Section: The Impact Of Political Ideology On Judgments and Decisionsmentioning
confidence: 96%
“…The share of liberals among early adopters of private solar panels was higher than the share of conservatives [12]. Liberal ideology and orientation to liberal parties was associated with elevated support for renewable energy projects and policies, as well as with stronger support for the Swiss Energy Act [3,13,14].…”
Section: The Impact Of Political Ideology On Judgments and Decisionsmentioning
confidence: 96%
“…Demographics may play an important role in local acceptance. One study that relied on a national survey found higher support for wind energy among males and White people; and lower support from those who identified as Republicans, were more conservative, or lived in the Northeast ( 19 ). Several other papers find a political divide, with greater opposition from conservatives ( 20 ) and greater support from liberals ( 21 ).…”
mentioning
confidence: 99%
“…Wind projects’ location may also affect support, with some regions being more supportive or hostile to projects. Several studies have found that individuals living closer to wind energy facilities are less supportive of projects ( 5 , 19 , 27 ), suggesting wind projects in remote areas may receive higher support. Land use may also affect support.…”
mentioning
confidence: 99%
“…Globally, governments support the development of wind power to mitigate the negative externalities of traditional fossil fuel electricity generation such as CO 2 emissions and greenhouse gasses [20]. Although wind energy has made great advances, coal is still the largest source of electricity in many industrialized countries [21,22]. Fossil fuel power plants are the primary source of greenhouse gases (GHG) in many countries [23].…”
Section: Development Motivationsmentioning
confidence: 99%